1993
DOI: 10.1021/bi00060a030
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic charybdotoxin-iberiotoxin chimeric peptides define toxin binding sites on calcium-activated and voltage-dependent potassium channels

Abstract: Charybdotoxin (ChTX) and iberiotoxin (IbTX) are highly charged peptidyl toxins which exhibit 68% sequence identity and share a similar three-dimensional structure. Despite these structural similarities, IbTX and ChTX differ in their selectivity for two types of potassium channels; large conductance calcium-activated potassium (maxi-K) channels and slowly inactivating voltage-gated (Kv1.3) potassium channels. ChTX blocks with high affinity both maxi-K and Kv1.3 channels, while IbTX blocks the maxi-K but not the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(52 citation statements)
references
References 30 publications
1
51
0
Order By: Relevance
“…1D). The k on value of 9.55 ϫ 10 7 M Ϫ1 s Ϫ1 determined with this relationship is higher than typical values reported for peptide-channel interactions (Park and Miller, 1992a,b;Giangiacomo et al, 1993;Mullmann et al, 1999) but is similar to the values determined for the ShK toxin (Middleton et al, 2003) and Pi2 (Péter et al, 2001), with picomolar affinities for Kv1.3.…”
Section: Discussionsupporting
confidence: 69%
“…1D). The k on value of 9.55 ϫ 10 7 M Ϫ1 s Ϫ1 determined with this relationship is higher than typical values reported for peptide-channel interactions (Park and Miller, 1992a,b;Giangiacomo et al, 1993;Mullmann et al, 1999) but is similar to the values determined for the ShK toxin (Middleton et al, 2003) and Pi2 (Péter et al, 2001), with picomolar affinities for Kv1.3.…”
Section: Discussionsupporting
confidence: 69%
“…Although ChTX was initially regarded as a specific blocker of the large conductance Ca2+ -dependent K+ channels (Miller et al, 1985), it has recently been shown that some cloned, voltage-gated K+ channels are also very sensitive to ChTX (Stuhmer et al, 1989;Grissmer et al, 1994). As we have shown, however, the major current observed in these cells was also sensitive to IbTX, an agent which does not affect voltagegated channels (Galvez et al, 1990;Giangiacomo et al, 1993).…”
Section: Discussionmentioning
confidence: 62%
“…3B) Target sizes are mean ± SEM from independent determinations made using either three (t) or four (*) different smooth muscle sarcolemmal membrane preparations. Table 1. dependent K+ channel, K,1.3, in neuronal tissue and lymphocytes (19,(24)(25)(26). For example, it has been shown with rat brain synaptosomal membranes that I251-ChTX binds to a single class of sites which display the pharmacological properties characteristic of the K,1.3 channel (19).…”
Section: Resultsmentioning
confidence: 99%